Mapping and Monitoring of Ravines Using Remotely Sensed Data - Karale, R.L; Saini, K.M.; Narula, K.K. (Journal of Soil and Water Conservation, 2022)
Ravines, comprising intricate net work of gullies, not only represent a locked-up production potential but also pose serious socio-economic problems. A camprehensive strategy for survey, monitoring and planning is needed to check the spread of ravines and to restore them to their production potential.Ravinous lands along Maleni river,a tributary of Chanibal in Ratlam and Ujjain districts of Madhya Pradesh have been characterised and mapped using Remote Sensing techniques and based on morpho- metrics they were classified into reclamability groupings. The spread of ravines over aperiod of 21 years was assessed using multistage and multidate remotely sensed data.Panchromatic BW aerial photographs of 1964 on 1 : 15,000 were used for differentiating ravine classes and Landsat TM false colour composite of 1985 in the enlarged scale of 1 : 250,000 was employed to assess spread of ravines. Adequate ground truth was used in ascertaining the morphometrics and finalizing the ravine maps.The results revealed that wheres PAN BW aerial photographs facilitated differentiation of five ravine reclamability groups, Landsat FCC failed to offer consistently reliable clues for this purpose. The ex- tent of ravinous lands as portrayed oil 1964 aerial photographs when compared with Landsat generated ravine map suggest encroachment of ravines on the neighbouring agricultural lands to the extent of 3 to 11 per cent in the different parts of the area over a period of 21 years.